Growth promotion and modulation of the soybean microbiome INTACTA RR PRO with the application of the fungi Trichoderma harzianum and Purpureocillum lilacinum - Rigobelo, Everlon Cid [UNESP]; de Carvalho, Lucas Amoroso Lopes [UNESP]; Santos, Carlos Henrique Barbosa [UNESP]; Frezarin, Edvan Teciano [UNESP]; Pinheiro, Daniel Guariz [UNESP]; Nicodemo, Daniel [UNESP]; Babalola, Olubukola Oluranti; Desoignies, Nicolas (Springer Nature, 2024)
Soybean is an economically important crop for animal and human nutrition. Currently, there is a lack of information on the effects of Trichoderma harzianum and Purpureocillum lilacinum on INTACTA RR PRO transgenic soybean plants. The present study evaluated the application of T. harzianum and P. lilacinum under field conditions. The results revealed a significant increase in soybean yield at 423 kg ha−1 in response to the application of P. lilacinum compared with the control treatment. In addition, the application of P. lilacinum promoted a significant increase in phosphorus levels in the plant leaves, and there were significant correlations between the increase in taxon abundance for the genus Erwinia and productivity and the average phosphorus and nitrogen content for the plant leaves, for the taxon Bacillus and nitrogen content and productivity, and for the taxon Sphingomonas and nitrogen content. The Bradyrhizobium taxon was identified in the P. lilacinum treatment as a taxon linking two different networks of taxa and is an important taxon in the microbiota. The results show that the application of the fungus P. lilacinum can increase the productivity of soybean INTACTA RR PRO and that this increase in productivity may be a function of the modulation of the microbiota composition of the plant leaves by the P. lilacinum effect.
Keywords: Decreased environmental impact; Plant growth-promoting fungi; Reduction in production cost; Sustainability